A study on the shared values and organizational climate at the YKS Oil Manufacturing, Incorporated - Yaokasin, Jerry T. (1990)
A study was conducted from December, 1989 to January, 1990, at the YKS Oil Manufacturing, Incorporated to determine the organizational climate at the company, the values being shared by its employees which directly affect such climate. It also determined the differences in perceptions of organizational climate and shared values between the labor and management sub-groups in the company.